Do firms prefer one form of accounting gimmick over other to meet peer performance? - Bansal, Manish (Penerbit Universiti Kebangsaan Malaysia, 2021)
The current study explores whether firms engage in classification shifting to meet industry-average profitability. The study examines the different alternatives under classification shifting for meeting industry numbers. Based on a sample of 15,616 firm-years, results exhibit that firms misclassify the cost of goods sold as a non-operating expense to meet the industry’s average gross margin ratio. Further empirical evidence provides that firms prefer shifting expenses over shifting revenues to meet the industry’s average profitability. Overall, results imply that peer performance is an important benchmark, and firms strive to achieve the same by engaging in different shifting strategies. The study is among the pioneering attempts that document a form of classification shifting where gross profit and core earnings both change as an effect of misclassification. The findings have important implications for auditors, investors, and analysts.